Effect of lacZY-marking of the 2,4-diacetyl-phloroglucinol producing Pseudomonas fluorescens-strain 5-2/4 on its physiological performance and root colonization ability - ALSANIUS, Beatrix Waechter; HULTBERG, Malin; ENGLUND, Jan-Eric (Microbiological research, 2002)
Transgenic Pseudomonas fluorescens 5-2/4 with reinforced 2,4-diacetyl phloroglucinol (phl) production had shown increased biocontrol ability towards Pythium ultimum (Pu), but inferior root colonization ability compared to its wild type 5.014. Therefore, enhanced root colonization ability of the transgenic strain by repeated inoculation and reisolation on tomato plants was suggested. As a preparation for repeated inoculation and reisolation cycles, the construction of a negative control of the transgenic strain 5-2/4 by marking with lacZY and screening for a mutant possessing qualities comparable to 5-2/4 was performed. Morphologically, colonies of all of the 11 selected mutants were similar on MLXgal medium. The root colonization ability of two of the lacZY-marked strains (mutants 1 and 10) was comparable to the parental strain. These were also able to compete with the resident microflora of tomato seedlings to the same extent as the parental strain. Five mutants were excluded due to lower growth rates on Yeast Malt, King's B Medium (KB) and 0.1 Tryptic Soy Agar (mutant 4, 5 and 8), excessive growth and higher siderophore production on KB (mutant 10) and increased protease production (mutant 2). With respect to in vitro-antagonism of Pu, no differences could be found between the target strain and mutants 1, 3, 6, 7 and 9. Examination of sole carbon source utilization of these five lacZY-marked strains revealed a significantly higher utilization of alpha-D-lactose and lactulose compared to 5-2/4. However, significant differences could be found for 51% of the utilized carbon sources. Cluster analysis showed a high degree of similarity between 5-2/4 and mutant 1 both when analyzed with and without alpha-D-lactose. As mutant 1 also represented the colonization pattern most similar to the parental strain 5-2/4, it presents a presumptive subject for a negative control in the following inoculation and reisolation studies on tomato.